MINDING ILLNESS: Toward A Philosophy of Health - Thasneem, Raheema; Balakrishnan, Vinod (Journal of Dharma, 2022)
This paper revisits the phenomenology of illness by analyzing competing philosophies of health that are deeply rooted in human experience. The non-clinical approach of the paper de-essentializes the experience of illness to construct a positive philosophy of life. It juxtaposes two opposing perspectives on illness: one, Edmund Pellegrino’s, in which the body is the centre of all experiences, and the other is the alternative philosophical position of Philipose Mar Chrysostom, which moves beyond mere wellness of the human body to propose an alternative bioethical position which emphasizes the role of the mind in the act of healing.